Hepatobiliary scintigraphy to evaluate liver function in associating liver partition and portal vein ligation for staged hepatectomy: Liver volume overestimates liver function - Olthof, Pim B.; Tomassini, Federico; Huespe, Pablo E.; Truant, Stephanie; Pruvot, François-René; Troisi, Roberto I.; Castro, Carlos; Schadde, Erik; Axelsson, Rimma; Sparrelid, Ernesto; Bennink, Roelof J.; Adam, Rene; et al. (Surgery, 2017)
Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) induces a rapid and extensive increase in liver volume. The functional quality of this hypertrophic response has been called into question because ALPPS is associated with a substantial incidence of liver failure and high perioperative mortality. This multicenter study aimed to evaluate functional liver regeneration in contrast to volumetric liver regeneration in ALPPS, using technetium-99m hepatobiliary scintigraphy and computed tomography volumetry, respectively. Patients who underwent ALPPS and hepatobiliary scintigraphy in 6 centers were included. Hepatobiliary scintigraphy data were analyzed centrally at the Academic Medical Center in Amsterdam according to established protocols. Increase in liver function as measured by hepatobiliary scintigraphy after stage 1 of ALPPS was compared with the increase in liver volume. In addition, we analyzed the impact of liver function and volume on postoperative outcomes including liver failure, morbidity, and mortality. In 60 patients, future liver remnant volume increased by a median 78% (interquartile range 48–110) during a median 8 (interquartile range 6–14) days after stage 1, while function as measured by hepatobiliary scintigraphy increased by a median 29% (interquartile range 1–55) throughout 7 days (interquartile range 6–10) in the 27 patients with paired measurements. After stage 2 of ALPPS, liver failure occurred in 5/60 (8%) patients, severe complications in 24/60 (40%), and mortality occurred in 4/60 (7%). In ALPPS, volumetry overestimates liver function as measured by hepatobiliary scintigraphy and may be responsible for the high rate of liver failure. Quantitative liver function tests are highly recommended to avoid post hepatectomy liver failure.